ANALISIS NILAI RELIGIUS DALAM NOVEL CINTA YANG TAK BIASA KARYA NATTA REZA DAN WARDAH MAULINA - Ahmad Ilzamul Hikam; Delilatul Adawiyah; Rofiatus Undayani (Universitas Batanghari, 2022)
This study aims to examine the religious values contained in the novel Cinta Yang Tak Biasa by Natta Reza and Wardah Maulina. This study used a qualitative method with literally sociological approach. Data collection is carried out interactively and and taken place continuously until it is complete, so that the data is saturated. The results of the study indicate that the religious values contained in the novel Cinta Yang Tak Biasa by Natta Reza and Wardah Maulina consist of three aspects, namely: the relationship between humans and God, the relationship between humans and humans, and the relationship between humans and himself. With this research, it is hoped that the next researchers will be able to make more in-depth research, this research is expected to be a reference material to add insight into religious values.